Token Phenomenon in Participatory Architectural Design and Sulukule Urban Transformation as a Tokenism Example - Fareghi Bavilolyaei, Baharak; Okem, Selim (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2018)
The participation approach within architectural design is assessed under a wide conceptual frame and known as a title generally confirmed and rately criticised. This paper discusses how the concept of participation may be used as a means of legitimization by the power holders instead of being favoured as a tool for democratic and transparent policy formation in the decision-making processes. The use of participation, which is a subject of research in sociology studies, but as a means of legitimization has been explained by Kanter (1977, 1993) through the concept of 'token'. The concept 'token' is identified throughout this text as a misleading symbol value whereas the 'tokenism' as a method is referred to as alleged participation. The tokenisim (i.e. alleged participation) is a subject not limited only with sociology whereas it may be spotted in architectural projects; thus, this document examines the Sulukule urban transformation process to exemplify this kind of participation. The study analyzes the theoretical claims of Arnstein, Lefebvre and Kanter with regard to the participation and accordingly the wording attempts to identify the general characteristics of tokenism cases in architectural projects which target user participation however include the intentions of power holders as accompanied by token impacts.
Keywords: Pluralism; popularism; participatory architectural design; tokenism; token; Architecture